Iraqi Feasibility Driving Licence International Feasibility Driving Licence (IFDL) Version 1.0: An Applied Study on University of KUFA - Alfadhel, Ali Abdulhussein Khaleel; Khadom, Hayder Jawad; Ali, Maher Naji; Rahi , Mohamed Ghali (Journal of Ecohumanism, 2024)
The research aims to establish a center that grants certification and professional practice in preparing feasibility studies and project evaluation under the name of the International Feasibility Driving License (IFDL) program. This is a unique initiative. The researcher arrived at several conclusions and recommendations, the most important of which are: adopting the idea of creating the Iraqi License and the International Economic Feasibility License project based on the analysis of internal and external environments will contribute to directing investment optimally in Iraq. Based on the financial ratios extracted, the project was found to be highly feasible, with a payback period of only two years and a return on investment of 48%. The researcher recommended the approval and adoption of this project by the University of Kufa Council for the year 2024, with the commencement of activities in 2025. The project will operate as one of the consulting offices affiliated with the University of Kufa according to the amended Law of Scientific and Advisory Service Offices in Higher Education and Scientific Research Institutions No. 7 of 1997 in Iraq. After the approval of this initiative, efforts will be made to obtain international accreditation by applying the necessary accreditation standards and to enhance the expertise of the proposed project with foreign and Arab experiences through organizing conferences and awareness seminars to market the idea.